2015
DOI: 10.1186/s13075-015-0663-9
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal polysaccharide vaccination in adults undergoing immunosuppressive treatment for inflammatory diseases – a longitudinal study

Abstract: IntroductionPatients undergoing immunosuppressive therapy are at increased risk of infection. Community-acquired pneumonia and invasive pneumococcal disease account for substantial morbidity and mortality in this population and may be prevented by vaccination. Ideally, immunization to pneumococcal antigens should take place before the start of immunosuppressive treatment. Often, however, the treatment cannot be delayed. Little is known about the efficacy of pneumococcal vaccines during immunosuppressive treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 32 publications
2
55
0
4
Order By: Relevance
“…In this cohort, a direct correlation was shown between the postvaccination levels of antipneumococcal antibodies and the risk of pneumococcal infections: more robust antibody responses after vaccination with PCV7 were associated with lower risk of serious pneumococcal infections 123. The humoral immunogenicity and safety of PPSV23 were demonstrated in RA,76 81 109 112 113 119 124 SLE,116 125 134 and, to a limited extent, in SpA and other rheumatic diseases 115. The long-term immunogenicity of PPSV23 was evaluated in two studies in patients with RA, treated with MTX121 and biologics 130.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…In this cohort, a direct correlation was shown between the postvaccination levels of antipneumococcal antibodies and the risk of pneumococcal infections: more robust antibody responses after vaccination with PCV7 were associated with lower risk of serious pneumococcal infections 123. The humoral immunogenicity and safety of PPSV23 were demonstrated in RA,76 81 109 112 113 119 124 SLE,116 125 134 and, to a limited extent, in SpA and other rheumatic diseases 115. The long-term immunogenicity of PPSV23 was evaluated in two studies in patients with RA, treated with MTX121 and biologics 130.…”
Section: Resultsmentioning
confidence: 73%
“…From the previous recommendations and up to August 2018, 34 studies53 76 81 83 84 105–133 and two meta-analyses45 77 have been published on the efficacy, immunogenicity and safety of PPSV23 and the conjugated vaccines PCV7 and PCV13, including evaluation of a combined strategy (tables 7 and 8). 106 128 133…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a retrospective study on the long-term effect of PPSV23 in RA patients treated with MTX showed a relative risk of 9.7 to develop pneumonia in non-vaccinated patients 124. The humoral immunogenicity and safety of the PPSV23 has been demonstrated in RA,64 87 125–129 SLE,130–132 and to a limited extent in SpA and others 133. The long-term immunogenicity of PPSV23 has been evaluated in two studies, in RA patients treated with MTX124 and biologics, respectively 134.…”
Section: Resultsmentioning
confidence: 99%
“…Примечательно, что в отличие от имму нокомпрометированных лиц (длительно и часто болеющих детей) [9] Анализ значений СГТА у ВИЧ позитивных пациентов в зависимости от стадии инфекции выявил достоверные отличия в продолжитель ности поствакцинального иммунитета. У па циентов с 3 й и 4А стадиями ВИЧ инфекции до проведения иммунизации отсутствовали ста тистически достоверные различия в показате лях СГТА, содержание IgG антител к СП S. рneu moniaе составило 49,8 ± 2,3 и 45,8 ± 1,2 УЕ/мл соответственно (см.…”
Section: иммунизацияunclassified
“…Полученные ре зультаты подтверждают мнение зарубежных авторов о вакцинации ВИЧ позитивных па циентов от различных патогенных агентов, где указывается, что при прогрессировании инфекции концентрация поствакцинальных антител значительно снижается, т.е. исчезает поствакцинальный иммунитет [9,10]. Также имеются работы, в которых отмечается сни жение эффекта от иммунизации, если паци ент с ВИЧ инфекцией злоупотребляет алко голем или никотином [11].…”
Section: рис 2 профилактическая эффективность пневмококковой вакцинunclassified